Macroeconomic factors and LQ45 stock price index: evidence from Indonesia - Utomo, Sugeng Hadi; Dwi Wulandari; Narmaditya, Bagus Shandy; Handayati, Puji; Ishak, Suryati (Business Perspectives, 2019)
This paper provides the relationship between macroeconomic variables, including exchange rate, BI rate and inflation, and stocks performance, particulary bluechip stocks listed in LQ45 index in Indonesia Stock Exchange. The study particularly gives insights on bluechip stocks listed in LQ45 stock price index in Indonesia Stock Exchange between 2015 and 2017. The data were obtained from various sources during the period, including the Indonesia Stock Exchange (IDX), the Central Bank of Indonesia (BI), and the Ministry of Trade. This study followed a Vector Error Correction Model (VECM) attempting to estimate the relationship between variables both in the short term and in the long term. The findings of the study showed that in the long run, exchange rate, BI rate and inflation have a negative impact on stock market performance, particularly on LQ45 index in Indonesia Stock Exchange. It implies that an increase in macroeconomic variables results in the decline of stock market performance. Meanwhile, in the short run, two variables, namely the exchange rate and inflation, positively affect stock market performance in Indonesia. On the contrary, the relationship between BI rate and stock market performance showed a negative correlation. These findings have significant implication for the understanding of how macroeconomic variables affect the stock market performance, particularly LQ45 price index in Indonesia Stock Exchange.